2023
DOI: 10.1101/2023.01.12.523789
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DENND2B activates Rab35 at the intercellular bridge regulating cytokinetic abscission and tetraploidy

Abstract: Cytokinesis is the final stage of cell division. Successful cytokinesis requires membrane trafficking pathways regulated by Rabs, molecular switches activated by guanine nucleotide exchange factors (GEFs). Late in cytokinesis, an intercellular cytokinetic bridge (ICB) connecting the two daughter cells undergoes abscission, which requires depolymerization of actin. Rab35 recruits MICAL1 to oxidate and depolymerize actin filaments. We report that DENND2B, a protein previously implicated in cancer, mental retarda… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…For instance, patients with a pathogenic missense variant in a gene involved in regulating cytokinesis exhibited intellectual disability and microcephaly ( 53 ). Recently, we identified that Rab35 is recruited to the cytokinetic bridge via its interaction with DENND2B, which functions as a GEF and effector for the GTPase ( 54 ), and promotes F-actin oxidation by Rab35 effector MICAL1 ( 30 ). It is likely that Rab35 R27H is not recruited to the cytokinetic bridge or is unable to promote successful cytokinetic abscission because of lack of interaction with effectors.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, patients with a pathogenic missense variant in a gene involved in regulating cytokinesis exhibited intellectual disability and microcephaly ( 53 ). Recently, we identified that Rab35 is recruited to the cytokinetic bridge via its interaction with DENND2B, which functions as a GEF and effector for the GTPase ( 54 ), and promotes F-actin oxidation by Rab35 effector MICAL1 ( 30 ). It is likely that Rab35 R27H is not recruited to the cytokinetic bridge or is unable to promote successful cytokinetic abscission because of lack of interaction with effectors.…”
Section: Discussionmentioning
confidence: 99%